A Rare Case of Double-System With Ectopic Ureteral Openings Into Vagina - Duicu, Carmen; Kiss, Eva; Simu, Iunius; Aldea, Cornel (Frontiers in Pediatrics, 2018)
The presence of an ectopic ureter may be indicated by continuous wetting, despite a normal voiding pattern, especially in girls. In most cases, an ectopic ureter is associated with a duplex collecting system and complete ureteral duplication. A 5-year-old girl presented with urinary incontinence regardless of the successful toilet training and a suspicion of left duplex kidney on a previous ultrasound. Contrast-enhanced computed tomography revealed a double left kidney with double ureters, both inserting together into the vagina. The surgical treatment consisted in the “en block” reimplantation of the ectopic ureters into the bladder, with complete resolution of the symptoms. The reported case does not represent just a typical presentation of a single ectopic ureter, as the duplex kidney system had ectopic both ipsilateral ureters (with insertion into the vagina). This case reminds us that congenital abnormalities of the genito-urinary tract should be considered in case of urinary incontinence and recurrent urinary tract infections.